A Review of the state-of-the-art of educational research : the Philippine experience, vol. 2 : educational testing evaluation and measurement. (Philippines : PRODED, 1986)
Research is rightly a cornerstone of educational planning, development, and evaluation, particularly where curriculum relevance, quality and effectiveness are the basic concerns of educational planners, practitioners and the clientele of educational institutions. The Program for Decentralized Educational Development (PRODED) of the Ministry of Education, Culture and Sports (MECS), the centerpiece of this decade's elementary education reform pro-gram, has among its objectives the following: to redress disparities in educational opportunities between and within regions; to improve the quality of elementary education; to improve the internal efficiency and effectiveness of the system and to strengthen management and planning capabilities. To achieve these objectives, there is a need for research-based knowledge which can provide direction for educational programs, projects, and activities.
A. Introduction -- B. Conceptual framework -- C. Methodology -- D. Presentation and discussion of results -- E. Conclusion -- F. Recommendation.
Includes bibliographical references.
Keywords: EDUCATIONAL RESEARCH